The Conflict Between Social Classes in Qur'anic and Marxist Expression: An Expressive and Interpretive Research - Makmun, Muhammad; Marpuah, Siti (RUSYDIAH: Jurnal Pemikiran Islam, 2024)
This article aims to present the expressions of the Qur'an and the thoughts of Karl Marx on the issue of social class conflict. In contexts where human differences can become sources of conflict and contention, often leading to mutual degradation and destruction, this study is crucial. This research employs the "expressive approach" and the "hermeneutic approach" to analyze the expressions of the Qur'an and Marx's thoughts on social class conflict. The findings indicate that the Qur'an addresses this issue within a religious context as guidance for humanity, acknowledging social disparities and affirming individual ownership rights without denying the existence of social class conflict. The Qur'an uses this conflict as an opportunity to return to tolerance, balance, and justice without rejecting or abolishing any social class. Conversely, Karl Marx discusses this theme in a political and economic context, recognizing social class disparities and striving to eliminate them to overcome the injustices perpetrated by the wealthy against the weak. He proposes communist ideology as a solution to create a classless social system, where thought, governance, and wealth are distributed equally, with political power that he considers ideal.